Manejo de una explosion del gusano cachon Erinnyis ello (L) (Lepidoptera: Sphingidae) - Bellotti, Anthony C. (International Center for Tropical Agriculture, 1981)
The management of a sudden high population of the cassava hornworm (Erinnyis ello) is discussed on the basis of data referring to those occurring in Santander de Quilichao in May 1980, in plantations at the exptl. station at the Centro lnternacional de Agricultura Tropical (CIAT), and in a neighboring commercial plantation. Likely causes of these high populations are explained and the following recommendations should be taken into account: (1) periodic inspection of crops; type BL light traps are recommended for this purpose; (2) egg hatching should be closely monitored since larvae are more susceptible to insecticides; (3) release of Trichogramma should be made on fresh layings; (4) application of Bacillus thuringiensis are more effective when applied during the 1st stage of development of E, ello. In the aforementioned population, 3 g B. thuringiensis/l of water + 0.5 cc of adjuvant were applied; excellent control was obtained. (CIAT)